Revisiting histories of anti-racist thought and activism. Issue 1 (2nd January 2020) - Bhattacharyya, Gargi; Virdee, Satnam; Winter, Aaron
ABSTRACT: This piece reconsiders histories of anti-racist thought and practice, including the linkages between anti-racisms and other traditions of liberatory thought. We argue that anti-racism should be understood as a strand in radical thought linking internationalism, institutional critique and street activism, in the process interfeeding with other social movements. The traditions of anti-racist thought discussed in this special issue exemplify these cross-cutting influences.